پاکستان میں اردو سیرت نگاری کے اسلوبیاتی رجحانات :ایک تحقیقی مطالعہ : STYLISTIC TRENDS IN URDU SEERAT WRITING IN PAKISTAN: AN ANALYTICAL STUDY (Al-Aasar, 2026)
This study examines the stylistic trends in Urdu Sirat literature in Pakistan, providing a comprehensive analytical perspective on its evolution, thematic patterns, and literary techniques. Urdu Sirat writing in Pakistan reflects a longstanding tradition of religious, historical, and ethical scholarship, blending narrative, didactic, and analytical styles. Through a detailed review of prominent Urdu Sirat authors, including their use of narrative, rhetorical, and expository methods, this research highlights the diversity of stylistic approaches employed to convey the life, teachings, and moral character of Prophet Muhammad ﷺ. The study also explores how historical context, literary conventions, and audience considerations have shaped the stylistic choices of Urdu Sirat writers in Pakistan. The findings demonstrate that Pakistani Urdu Sirat literature not only preserves historical and religious knowledge but also serves as a medium for moral, spiritual, and intellectual education, reflecting a unique interplay between literary creativity and scholarly rigor.